THE IMPLEMENTATION OF CLINICAL PROCEDURES IN THE VERTICAL REFERRAL SYSTEM IN A PRIMARY HEALTHCARE CENTER - Nadia Damayanti Soeripto (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2019)
Background: A referral system in the era of National Health Insurance starts from first-level primary health facility. The high number of referral in one of primary healthcare centers in Surabaya indicates that the implementation of the vertical referral system has not gone well.Aim: To determine the conformity of the vertical referral system to the clinical procedures at the general outpatient clinics of the the primary healthcare center based on the National Referral System Guidelines.Methods: This study was an observational descriptive study and used implementation research method, which conducted in August 2018. This study was conducted in one of primary healthcare centers in Surabaya. This study used triangulated data, such as the review of reference documents, interviews with referral officers, and direct observation.Results: Out of 7 regulations in the clinical procedures of referral system according to the National Referral System Guidelines, only 2 regulations were not run by the at the general outpatient clinics of the primary healthcare center. For example, patients being referred did not come to the primary healthcare center on their own instead of requesting their family to come. Also, the doctors in the primary healthcare center referred the patients by themselves. However, according to the guidlines, before referring patients, the doctors should contact the referred health facilities.Conclusion: The implementation of clinical procedures in the vertical referral system in the primary healthcare center in Surabaya is broadly in accordance with the existing regulations and guidelines. However, it is necessary to do some improvement. It is recommended that they should re-contact the referral health facility before referring the patients to improve the quality of communication and provide more education to the patients’ family so that they bring the patients to do check-up when the the referral is extended. Keywords: Clinical procedure, Primary healthcare center, Vertical referral system.